Creating GIF animations : using Photoshop and other Adobe apps. (Apress, 2022)
Learn what GIF animations are, why they are so popular, and how you can easily create your own for your website, email, or social media page using Photoshop and other Adobe apps. Author Jennifer Harder begins by providing a brief history of GIF animation before discussing its common uses on today's social media platforms, as well as its advantages and disadvantages. She'll then demonstrate how to prepare images using the Photoshop Timeline and Layers panels as they relate to GIF creation and how to transform graphics on each layer to create movement between frames. You'll also gain an understanding of the ideal Export settings for optimizing quality and file size for online use. Additionally, you'll see how to create GIF animations from short video clips and master the use of Illustrator to copy created stills for use in Photoshop. Finally, you'll explore other Adobe applications that can be used to create GIF animations as well as GIF alternatives for the Web. After completing this video, you will be able to create your own GIF animations for informational, promotional, or entertainment purposes. What You will Learn Understand GIF animation and its relevance in today's social media environment Optimize quality and file size for your GIF online Transform your graphics on each layer to create movement between frames Who Is This Video For Students, graphic artists, photographers, video artists/animators, and web designers with basic knowledge of Photoshop.